Heterotrophy of Oceanic Particulate Organic Matter Elevates Net Ecosystem Calcification. Issue 16 (31st August 2019) - Kealoha, Andrea K.; Shamberger, Kathryn E.F.; Reid, Emma C.; Davis, Kristen A.; Lentz, Steven J.; Brainard, Russell E.; Oliver, Thomas A.; Rappé, Michael S.; Roark, E. Brendan; Rii, Yoshimi M.
Abstract: Coral reef calcification is expected to decline due to climate change stressors such as ocean acidification and warming. Projections of future coral reef health are based on our understanding of the environmental drivers that affect calcification and dissolution. One such driver that may impact coral reef health is heterotrophy of oceanic‐sourced particulate organic matter, but its link to calcification has not been directly investigated in the field. In this study, we estimated net ecosystem calcification and oceanic particulate organic carbon (POCoc ) uptake across the Kāne'ohe Bay barrier reef in Hawai'i. We show that higher rates of POCoc uptake correspond to greater net ecosystem calcification rates, even under low aragonite saturation states (Ωar ). Hence, reductions in offshore productivity may negatively impact coral reefs by decreasing the food supply required to sustain calcification. Alternatively, coral reefs that receive ample inputs of POCoc may maintain higher calcification rates, despite a global decline in Ωar . Plain Language Summary: Coral reefs are threatened by climate change stressors including ocean acidification and ocean warming. One way to measure and monitor coral reef health is to estimate coral reef calcification, which is influenced by several environmental factors including light, temperature, pH, and nutrient availability. By understanding the effects of these factors on calcification, we can better predict how corals will respond to climate change. One potentially important factor for calcification that has not been investigated in the field is coral reef ecosystem feeding on particulate organic matter supplied from offshore (i.e., oceanic particulate organic matter). In this study, we estimated net ecosystem calcification and oceanic particulate organic carbon (POC) uptake across the Kāne'ohe Bay barrier reef in Hawai'i. For the first time, we show a direct correlation between net ecosystem calcification and oceanic POC uptake, which suggests that the reef is using oceanic POC as an energy source to elevate calcification. However, since climate change reduces oceanic POC production through warming and stratification, our results imply coral reef calcification may decline. Alternatively, coral reefs located in regions of high oceanic productivity and that sustain greater rates of oceanic POC uptake may be able to maintain calcification longer into the future. Key Points: Oceanic particulate organic matter uptake elevates net ecosystem calcification, even under low aragonite saturation states The rates of net ecosystem calcification and oceanic particulate organic matter uptake are sensitive to changes in water flow speeds